One step away from extinction: a population genomic analysis of a narrow endemic, tropical plant species - Thais Martins Teixeira (2021)
Endemism, restrict geographic distribution, and small population size are relevant features for the assessment of extinction risk of species. Narrow endemic species can often occur in small population sizes, which implies higher risk of (local) extinction due to demographic and genetic factors. Therefore, conservation efforts for species on the verge of extinction should be based on genetic and/or ecological studies. Mimosa catharinensis Burkart (Fabaceae) is a critically endangered and extremely narrow endemic species from the Brazilian Atlantic Rainforest, with only one population (N=33). To provide genetic information to support conservation plans for M. catharinensis, we used the reduced-representation sequencing approach ddRADseq (double digestion Restriction Site associated DNA) to generate genome-wide high-throughput sequencing data. Our population genomic analysis showed that, regardless its extremely small population size, M. catharinensis is maintaining moderate levels of genetic diversity [uHE(0%missing data)=0.205, 95%CI (0.160, 0.250); uHE(30%missing data)=0.233, 95%CI (0.174, 0.292)], absence of inbreeding [F(0%missing data)=-0.145, 95%CI (-0.189, -0.101); F(30%missing data)=- 0.105, 95%CI (-0.199, -0.011)] and high outcrossing rates (t(0%missing data)=0.883, SE ± 0.0483; t(30%missing data)=0.909, SE ± 0.011). Furthermore, demographic inferences suggest the occurrence of a recent bottleneck for the M. catharinensis population followed by a constant declining population. We emphasize that the results obtained in this study should be considered on conservation actions for M. catharinensis. Going forward, it is still needed to investigate important ecological factors such as the species' reproductive biology to support adequate conservation strategies in order to safeguard this unique genetic resource.